The Senegalese Sole Mx gene promoter contains a variable microsatellite region involved in the transcriptional - Álvarez-Torres, Daniel; Vieytes, Lisandro P; García-Rosado, Esther; Alonso-Sánchez, María del Carmen; Béjar-Alvarado, Julia (My University, 2015)
Interferons (IFNs) play a key role against viral infections by stimulating the expression of IFN stimulated genes, such as Mx. The transcriptional regulation of these genes in fish are poorly understood. The sequencing of the Senegalese sole (Solea senegalensis) Mx gene promoter revealed the presence of a guanosine-citosine rich region that contains a microsatellite, sited close to the translation start codon. The aim of the current study has been to determine the functional role of this region and to study its variability.
Keywords: Interferón; Peces - Enfermedades por virus; Senegalese sole; Mx gene; Promoter; microsatellite